2019
DOI: 10.1038/s41598-019-39041-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of lysophosphatidic acid-induced hypertensive response

Abstract: Lysophosphatidic acid (LPA) is a blood-derived bioactive lipid with numerous biological activities exerted mainly through six defined G protein-coupled receptors (LPA 1 -LPA 6 ). LPA was first identified as a vasoactive compound because it induced transient hypertension when injected intravenously in rodents. Here, we examined the molecular mechanism underlying the LPA-induced hypertensive response. The LPA-induced hypertensive response was significantly attenuated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 28 publications
3
26
0
1
Order By: Relevance
“…33 Notably, LPA species containing an unsaturated acyl chain are potent vasoconstrictors but whether cognate GPCRs for LPA (LPA 1-6 ) mediate these effects is uncertain. 31,34 We found that LPA (C18:1) constricted skeletal muscle arterioles isolated from WT but not from TRPV1-null mice confirming a selective action at TRPV1 (Fig. 5, A and B).…”
Section: Lysophosphatidic Acid Constricts Arterioles and Increases Blsupporting
confidence: 52%
See 1 more Smart Citation
“…33 Notably, LPA species containing an unsaturated acyl chain are potent vasoconstrictors but whether cognate GPCRs for LPA (LPA 1-6 ) mediate these effects is uncertain. 31,34 We found that LPA (C18:1) constricted skeletal muscle arterioles isolated from WT but not from TRPV1-null mice confirming a selective action at TRPV1 (Fig. 5, A and B).…”
Section: Lysophosphatidic Acid Constricts Arterioles and Increases Blsupporting
confidence: 52%
“…We examined lysophosphatidic acids (LPA), a vasoconstrictor lipid species generated by platelets and atherogenic plaques (31,32), potentially activating TRPV1 (33). Notably, LPA species containing an unsaturated acyl chain are potent vasoconstrictors but whether cognate GPCRs for LPA (LPA 1-6 ) mediate these effects is uncertain (31,34). We found that LPA (C18:1) constricted skeletal muscle arterioles isolated from WT but not from TRPV1-null mice confirming a selective action at TRPV1 (Fig.…”
Section: Lysophosphatidic Acid Constricts Arterioles and Increases Blmentioning
confidence: 84%
“…Lysophosphatidic acid promotes transient hypertension mainly via the Gα 12/13 -coupling LPA4 receptor, one of five LPA receptors (LPA1-4 and LPA6). The ROCK inhibitor Y-27632 successfully suppresses LPA-induced hypertension, suggesting that LPA increases blood pressure via the Gα 12/13 -Rho/ROCK pathway 122 . Angiotensin II is an important factor for increasing blood pressure via AT1.…”
Section: Role Of Gα 12 In Cardiovascular Diseasementioning
confidence: 99%
“…Neurons (DIV 10, ~5 × 10 5 cells) derived from wild-type mice were treated with 10 µM LA or CLA for 24 h. Lipids were recovered with acidic methanol (pH 4.0, 200 µL) that contained 1 µM 17:0-LPC as an internal standard and stored at -80°C. LC-MS/MS analysis was performed as described previously (Kano et al, 2019) with some modifications. Briefly, LC was performed using a C18 column (CAPCELL PAK C18 (1.5 mm I.D.…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%